Comparative Characteristics of Hemostasis During Vaginal Hysterectomy - Andrei N. Plekhanov; Vitalii F. Bezhenar; Tat’yana A. Epifanova; Fedor V. Bezhenar (Кубанский научный медицинский вестник, 2019)
Aim. To compare the results of surgical treatment using bipolar hemostasis and traditional ligation of ligaments and blood vessels in vaginal hysterectomy.Material and methods. Fifty patients with benign uterine disease underwent vaginal hysterectomy using electrosurgery (n = 29) or conventional suture ligation (n = 21 controls).Results. Postoperative pain (especially on the fi rst day) was decreased in the electrosurgery group (5.50 ± 1.43 VAS points) as compared to the control group (7.64 ± 0.58 points), p < 0.001. Intraoperative blood loss was signifi cantly lower in electrosurgery group (82.86 ± 22.58 ml) than in the control group (226.36 ± 129.12 ml), p < 0.001. Operating time was signifi cantly shorter in the main group than in the controls (65.36 ± 20.9 min vs. 86.59 ± 40.19 min, p < 0.05). On average, 2.75 ± 1.11 suture packages were used with bipolar coagulation, 6.00 ± 1.93 in the controls (p < 0.001). Hospital stay was similar for both groups. Adverse event rates did not differ signifi cantly.Conclusions. Bipolar coagulation with the TissueSeal Plus proved to be more effi cient or identical to traditional suture ligation. Intraoperative blood loss, postoperative pain and the duration of the operation were less, while the complications were identical for both groups. In addition, bipolar coagulation was easier to use and cost effective. These fi ndings prove the feasibility and effectiveness of the use of electrosurgical techniques to perform hysterectomy and its further study